Seroprevalance of Influenza A in swine population of Rangamati and Khagracchari districts - Uddin, Md. Karim; Ahasan, Md. Shamim; Islam, Mohammad Rafiqul; Islam, M. M. Mafizul; Hoque, Md. Fazlul (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study is conducted to assess the seroprevalence and associated risk factors (e.g., age, sex, bio-security practices and management system) of Influenza A virus in swine population of Rangamati and Khagracchari Districts Materials and methods: Prevalence study Influenza A in swine population was conducted over a period of six months Rangamati and Khagracchari Districts between July to December 2013. 180 blood samples were collected from pigs, and the samples were tested for the detection of Influenza antibody using Indirect ELISA method. Results: Total numbers of samples were 180 and numbers of positive cases were 22.Then the overall seroprevalence between the aforesaid districts was found to be 12.22%. Results of the investigation revealed that the seroprevalence of influenza A was 15% in Rangamati district, 10% in Khagraccharidistrict . The highest seroprevalence was found in Rangamati district (15%) and the lowest seroprevalence was (10%) found in Khagracchari district. On the basis of sex, seroprevalence rate of influenza A was found 14.29% in male pigs and 9·76% in female pigs. Conclusion: The study confirms that influenza virus is circulating in the pig populations of hill tracts area of Bangladesh. Our study had a number of limitations. Veterinarians, researchers and health officials will get new information from this research which will be helpful for developing prevention strategy for combating against this disease. http://doi.org/10.5455/javar.2018.e269